YAE and Teachers Training: an analytical study of the pedagogical projects of teaching degrees at the CFP/UFCG - Everton Vieira da Silva; Jefferson Antônio Marques; Antunes Ferreira da Silva (Universidade Estadual de Alagoas, 2020)
Teaching degrees have presented curriculum and approaches that value the teaching process and the learning of a set of theoretical and practical knowledge pointed out as a basis for the training of teachers regarding specific curriculum components. However, it is necessary to analyze whether this set includes the training needs to teach in specific segments, such as Youth and Adult Education. Characterized as an explanatory,bibliographic and documentary research, this study intends to understand how YAE has been approached in the training of teachers for basic education at the Teacher Training Center -UFCG, Campus Cajazeiras, where the pedagogical projects were analyzed, observing the existence the subject of YAE, whether mandatory or not, form of approach, as well as the focus given in each course and itsreflection in teacher education for basic education. The results showed that the majority of undergraduate courses in the institution do not have curriculum components related to YAE; however, the degrees in Physics and Pedagogy stand out for presenting rolls with historical contexts and characteristics of the modality, as well as descriptions related to the teaching and learning processes. Therefore, it is necessary for the undergraduate courses to consider the importance of YAE in their training programsand implement theoretical-contextual, didactic-pedagogical disciplines and supervised internships related to the segment.